Inquiry Learning Model to improve Social Studies Learning Outcomes in Class V SD Negeri 59 North Bengkulu - Lindawati Lindawati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
This Research aim to to increase process the study IPS of to be can please and make the student become active. Applying model the study Inquiry can improve the result learn the IPS of student in the class V SD Negeri 59 Bengkulu Utara of teaching year 2593 / 2594. This Research type is Classroom Action Research (PTK) by using model of Kemmis and Mc. Taggart, by subjek is research that is students in the class V SDN 59 Bengkulu Utara amounting to 23 student and object in this research is the make-up of result learn the student at subject IPS. Action conducted by during this research is study execution by using model Inquiry. Technique of data collecting used by is problem tes of[is breakdown of and Technique observation analyse the data conducted by dekriptif qualitative and quantitative descriptive Result of research indicate that through applying model the Inquiry in study IPS can improve the result learn the student. Make-Up of result learn this student is seen from the increasing of student ability in searching answer from problems of through various step in model Inquiry that is orient, formulating problem, formulating hypothesis, collecting data or information, conducting hypothesis test, and formulate the conclusion. With refer to the step in model inkuri of besides improving result learn also improve the student livelines in course of study of where student instructed to go it alone to to look for answers to question which have dirumusakan. Make-Up of result learn the student seen from the increasing of complete percentage result of tes student of where at cycle I from 74% and mount again at cycle II become 91%.Keywords: Model the Inquiry, Result of learning IPS.